Form and function of prologues in 19th century latin American grammars - Vila Rubio, Neus (Boletín de Filología, 2021)
Prologues are valuable pieces for the historiographic investigation about works that deal with linguistic aspects, that is, for Linguistic Historiography (HL). In this work we propose to examine this type of texts (paratexts) produced at one time: the 19th century; a space: Hispanic America; and a typology: works on grammar and orthography. All this from a precise and exhaustive analysis methodology, which will allow to establish what are the forms that such texts adopt, that is, their variants and representations, as well as the functions they perform in the contextual framework to which they are assigned, both intralinguistic: the works they surround, and extralinguistic: the sociocultural and political environment in which these works are produced. With this we intend to contribute to the historiography of linguistic ideas in relation to the Spanish languageand its grammar.